DNA damage repair machinery and HIV escape from innate immune sensing - Brégnard, Christelle; Benkirane, Monsef; Laguette, Nadine (Frontiers in Microbiology, 2014)
Viruses have been long known to perturb cell cycle regulators and key players of the DNA damage response to benefit their life cycles. In the case of the human immunodeficiency virus (HIV), the viral auxiliary protein Vpr activates the structure-specific endonuclease SLX4 complex to promote escape from innate immune sensing and, as a side effect, induces replication stress in cycling cells and subsequent cell cycle arrest at the G2/M transition. This novel pathway subverted by HIV to prevent accumulation of viral reverse transcription by-products adds up to facilitating effects of major cellular exonucleases that degrade pathological DNA species. Within this review we discuss the impact of this finding on our understanding of the interplay between HIV replication and nucleic acid metabolism and its implications for cancer-related chronic inflammation.